Can We Predict Which Pelvi-Ureteric Junction Obstruction Need Surgical Correction?: A Literature Review - Warman, Putri Liana; Sibarani, Jupiter (Journal of Neonatal Surgery, 2025)
Pelvi-ureteric junction obstruction (PUJO) is a condition in which an obstruction occurs at the junction where the ureter attaches to the kidney. Correct diagnosis and appropriate treatment plan for PUJO are required. However, to date, research on tools or indicators to assess which PUJO cases require a surgical approach is still very limited. This study aims to predict which pelvi-ureteric junction obstruction need surgical consideration. Literature obtained from the search results of Pubmed, Medscape, Science Direct, and Google Scholar electronic databases with some keyword used. From the beginning of 2018, 74 articles were collected through the electronic database of NCBI, OVID (Medline), Elsevier, and Pubmed. Following all the inclusion and exclusion criteria mentioned earlier, the final selection considered 10 literatures were eligible to be included in this literature review. The results of the literature review showed that 4 studies reported the need of surgery in PUJO can be predicted by urinary marker. 3 Studies reported GFR/DFR as predictor for need of surgery. The most reported parameter as predictor for need of surgery was APD that was reported by 5 studies. 2 studies reported nuclear imaging as predictor: 1 studies reported T1/2 washout, and the other study reported MAG-3 in combination with other parameter to form MAG-SOS score. Other ultrasonography parameters were reported by 3 studies: 1 study reported renal pyramidal thicknes, and 2 studies showed a predictive value of scoring system using ultrasonography parameters (Pyeloplasty Predictive Score and obstructive index). Several parameters could predict the need of surgery in PUJO, however we could not conclude which parameter have the higher predictive value. It may be better to use multiple parameters